Role of Notch2 pathway in mature B cell malignancies - Mesini, Nicolò; Fiorcari, Stefania; Atene, Claudio Giacinto; Maffei, Rossana; Potenza, Leonardo; Luppi, Mario; Marasca, Roberto (Frontiers in Oncology, 2023)
In last decades Notch pathway has been characterized as a key regulatory signaling of cell-fate decisions evolutionarily conserved in a variety of organisms and tissues. At the same time, many studies suggested a link between alterations of this signaling and tumor genesis or progression. Notch pathway in lymphopoiesis plays a fundamental role for a correct differentiation of T and B cells, but its deregulated activity leads to leukemic onset and evolution. Notch and its ligands Delta/Jagged exhibit a pivotal role in the crosstalk between leukemic cells and their environment. This review is focused in particular on receptor Notch2 activity. Notch2 pathway members have been reported to be mutated in Chronic Lymphocytic Leukemia (CLL), Splenic Marginal Zone Lymphoma (SMZL) and Nodal Marginal Zone Lymphoma (NMZL). CLL is a B cell malignancy, in which neoplastic cells co-evolve together with a supportive tumor microenvironment, promoting leukemia cell survival, growth and drug-resistance. SMZL is an indolent small B cell neoplasm deriving from lymphocytes of the splenic marginal zone and affecting spleen, bone marrow and peripheral blood. The prevalent molecular lesions found in newly diagnosed SMZL affect Notch2 and this subgroup is related with worse outcome. NMZL is a rare indolent B cell tumor that is distinguished from SMZL by different pattern of dissemination, which in the first case is mainly nodal. Notch2 is involved in the commitment of leukemic cells to the marginal zone as leading regulator of B cell physiologically differentiation. In this context a better understanding of Notch receptor family pathogenic role, in particular Notch2, is desirable because still incomplete, not only in B cell physiological development, but also in leukemia progression and resistance. Several therapeutic strategies capable to interfere with Notch signaling such as monoclonal antibodies, enzyme or complex inhibitors are being analyzed. Anyway study an appropriate pharmaceutical formulation is necessary, because a systemic inhibition of Notch signaling results in “on target” multiple toxicity. This is why to date there are still no Notch-targeted therapies approved, therefore an accurate analysis of Notch pathway could be useful to drive the discovery of new therapeutic targets and the development of more effective therapies.